THU0206 Population-based epidemiology and description of behcet's disease in the african descent population of martinique, french west indies. (23rd January 2014) - Deligny, C.; Antonio, L.; Merle, H.; Numéric, P.; Signate, A.; Dehlinger, V.; Jean Baptiste, G.; Arfi, S.
Abstract : Background: No study describes the frequency of Behcet's disease (BD) in the populations of African origin and its characteristics. Objectives: To retrospectively assess by retrieval of multiple sources, the epidemiology and characteristics of BD in the mainly African descent population of Martinique, a French Island in the Caribbean. Methods: In 2011 we consulted 5 different sources. Patients were included if they lived in Martinique, were classified as certain if they fulfilled the international criteria for BD. The diagnosis was considered only as probable if they had recurrent oral ulcers with at least one other international criteria but no other possible diagnosis. The incidence during the 1997-2011 interval and prevalence at December 31, 2010 were calculated. Basic and BD-related characteristics were recorded. Results: 48 patients were indicated as BD. Only 36 (female, n=22; male, n=14) fulfilled the criteria. Mean age at diagnosis was 38.5 years old (range: 8-64), 36.6 for women and 41.6 for men. Disease onset was over 50 years old for 7 patients. Mean time between first signs and diagnosis was 4.2 years (range: 0-22). Twenty eight began their disease between 1997 and 2011 allowing a total crude mean annual incidence estimation of 0.72 new cases/10 5 inhabitants (0.79/10 5 for female and 0.59/10 5 for males, 0.37/10 5 for certain cases and 0.35/10 5 for probable). In December 2010, 28 patients were alive, 5 lost to follow up and 3 deceased: the crude prevalence was estimated as 7.04/10 5 inhabitants (Female: 7.49; male: 6.51). Genital ulcers were found in 75.6%. Dermatological manifestations were: pseudofolliculitis (52%), erythema nodosum (13.5%). Pathergy test was done for 6 patients and positive for 4. Nine patients had ophthalmologic involvement: anterior uveitis (55.5%, n=5), panuveitis and posterior uveitis (11.1%, n=1 each), conjunctival ulceration (22.2%, n=2). Parenchymal brain involvement was more frequent than non-parenchymal (7 versus 3 patients) without any cerebral venous thrombosis. Rheumatic manifestations were occurred in 20 patients (55.6%) mainly females (60%): polyarthritis (38.9%), monoarthritis and spondylarthropathy (11.1% each). Deep vein thromboses were seen in 2 cases and superficial in 1, central retinal artery occlusion in 1 patient. The colon was involved in 6 cases and the ileo-cecal region in one. Conclusions: In Martinique, BD seems to be a rare disease compared to Mediterranean and most Asian countries. The incidence is comparable to Spain and Switzerland. The prevalence is higher than in most European countries and USA. Black population seems to have particular manifestations of BD: older age at onset and rare uveitis. Disclosure of Interest: None Declared